Dysphagia progression and feeding skills following pediatric alkali ingestion injury: two case reports. Issue 23 (6th November 2017) - Follent, Anna M.; Rumbach, Anna. F.; Ward, Elizabeth C.; Marshall, Jeanne; Dodrill, Pamela; Lewindon, Peter
Abstract: Purpose: There is limited information regarding the nature of dysphagia and feeding difficulties following alkali ingestion injury to inform multidisciplinary intervention. The aim was to describe the history and nature of chronic dysphagia and feeding difficulties in two children following severe alkali ingestion injury. Methods: Medical records, primary caregiver report, and clinical assessment were used to compile detailed case histories and assess current dysphagia and feeding skills. Results: Both cases demonstrated heterogeneous oral motor and feeding outcomes, including delayed oral motor skills, restricted dietary variety, and difficult mealtime behaviors that contributed to protracted recovery of age-appropriate PO intake. Both children required ongoing diet and/or fluid modification and supplemental non-PO feeding via gastrostomy at the time of review, that is, 2-year post-injury. Conclusions: Recovery from dysphagia post-alkali ingestion is protracted and complex. Dysphagia, delayed oral motor skills, and difficult mealtime behaviors may persist secondary to ingestion injury and its associated complications. These cases highlight the importance of considering early referral for feeding assessment and intervention to assist children and families with recovery. Progression through safe and effective oral (per os, PO) intake is needed, as well as provision of support for primary caregivers. Implications for Rehabilitation: Pediatric chemical ingestion injury can cause long-term dysphagia and long-term feeding difficulties Initial injury severity does not reliably correlate with eventuating level of aerodigestive impairment. Clinical and instrumental assessment is required to monitor swallow function to enable commencement of targeted rehabilitation when appropriate. Early involvement of a feeding therapist is recommended to minimize the long-term effects on oral motor skill development, progression to age-appropriate diet, and provision of family-centered care.